Effects of Single and Mixed Viral Infections in Quantitative and Qualitative Terms - Pandey, Vishesh; Gupta, Arohi (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Urdbean leaf crinkle virus (ULCV) is responsible for causing one of the most devastating and important disease of urdbean or black gram [Vigna mungo (L.) Hepper]. The disease is characterized by severe crinkling, puckering and rugosity of the leaves associated with significant reduction in yield. Effect of virus infection on protein content and catalase activity was studied in two cultivars of urdbean, viz. T-9 and IPU 94-1 'Uttara'. A remarkable increase in protein content due to virus infection was observed in both the cultivars of urdbean. Decreased catalase activity was detected in ULCV infected leaves over the control.